First-order spatial coherence measurements in a thermalized two-dimensional photonic quantum gas - Tobias Damm (Nature Portfolio, 2017)
Phase transitions in quantum matter are related to correlation effects and they can change the ordering of material. Here the authors measure the first-order spatial correlation and the de Broglie wavelength for both thermal and condensed form of a photonic Bose gas in a dye-filled optical microcavity.